2019
DOI: 10.3389/fmicb.2019.02043
|View full text |Cite
|
Sign up to set email alerts
|

SR-BI Interactome Analysis Reveals a Proviral Role for UGGT1 in Hepatitis C Virus Entry

Abstract: Hepatitis C virus (HCV) entry is mediated by multiple co-receptors including scavenger receptor class B, type I (SR-BI). To elucidate the interactome of human SR-BI, we performed immunoprecipitation (IP) experiment coupled with mass spectrometry (MS) analysis. UDP-glucose:glycoprotein glucosyltransferase 1 (UGGT1), a key component of calnexin cycle involved in protein glycosylation, was identified as a SR-BI-interacting protein. Silencing UGGT1 or N-glycosylation inhibitor treatment reduced SR-BI protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…hosts, leading to differential receptor avidity during viral infection [31][32][33][34][35][36][37][38] . The arenavirus Lassa virus preferentially enters cells that express α dystroglycan (α DG) modified with long chain matriglycans 39 .…”
Section: Host Heterogeneity In Receptor Glycosylation Receptor Glycomentioning
confidence: 99%
See 2 more Smart Citations
“…hosts, leading to differential receptor avidity during viral infection [31][32][33][34][35][36][37][38] . The arenavirus Lassa virus preferentially enters cells that express α dystroglycan (α DG) modified with long chain matriglycans 39 .…”
Section: Host Heterogeneity In Receptor Glycosylation Receptor Glycomentioning
confidence: 99%
“…2a). Glycosylation of human scavenger receptor class B type I (SR BI), an HCV co receptor 41,42 , is thought to be mediated by UDP glucose:glycoprotein glucosyltransferase 1 (UGGT1) 34 . Silencing of UGGT1 or inhibition of N linked glycosylation of SR BI reduces its expression, and this diminishes HCV entry 34 .…”
Section: Host Heterogeneity In Receptor Glycosylation Receptor Glycomentioning
confidence: 99%
See 1 more Smart Citation
“…Bi 3+ is also highly sought after in the cosmetic and pharmaceutical industries, where it is commonly incorporated into eye shadows, lipsticks and hair dyes to provide the desired aesthetic properties [ 22 ]. In the pharmaceutical industry, Bi 3+ is used as an active pharmaceutical ingredient, particularly for the treatment of syphilis, peptic ulcers and hypertension [ 23 , 24 ]. It has been found that Bi 3+ significantly improves the efficacy of various drugs, such as antibiotics and anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…UGGT is inhibited by its product UDP (8) and by the non-hydrolysable UDP-Glucose (UDP-Glc) analogue UDP-2-deoxy-2-fluoro-D-glucose (U2F) but neither molecule is specific. Selective and potent UGGT modulators would be important reagents for cell biology for interrogating the cell biology of the secretory pathway, as well as having therapeutic potential in several areas of medical science, such as virology (9)(10)(11), rare genetic disease (12,13) and cancer (14)(15)(16). Selective and potent UGGT activity modulators also have potential applications in biotechnology and agricultural science (17)(18)(19)(20).…”
mentioning
confidence: 99%